Impact of COVID-19 Lockdown on Depression Severity and the Use of Drugs Among University of Ibadan Students - Abdulhammed Opeyemi Babatunde; Lordstrong Akano Olaniyi; AbdulSobur Olatunde Abdulazeez; Yeshua Ayokun Adedeji; Boluwatife Adefunke Bolatito; Christabel Ijeoma Uche-Orji; Adeniyi Abraham Adesola; Habib Ayomide Shobanke; Dimeji AbdulSobur Olawuyi; Dolapo Michael Babalola (University Library System, University of Pittsburgh, 2022)
Background: Since the declaration of COVID-19 as a pandemic, measures such as nationwide lockdowns have been implemented. The sudden disruption of activities coupled with fear could trigger or aggravate mental illnesses and consequently, increase substance use as a coping mechanism. This study then sought to assess the impact of the lockdown on depression and substance use amongst students in a tertiary institution in Ibadan city, Nigeria. Methods: A self-administered 26 questions online questionnaire was employed for data collection of socio-demographic characteristics, Patient Health Questionnaire (PHQ-9) to assess depression, and a section on the use of psychoactive drugs during lockdown. Data were statistically analyzed using IBM's SPSS and Microsoft Excel. Results: We gathered 102 responses, 54.9% were males. Most of the respondents had mild depression (41.2%), followed by 36.3% that reported not having an episode of depression, 15.7% moderate, 4.9% moderately severe, and 2% severe depression. Female had more depressive episodes than males (p=0.185). Only 4% reported substance use since the pandemic, all were male. At a 95% confidence interval, there was no significant association between the level of depression and any socio-demographic characteristics of students and between the level of depression and drug use. Conclusions: According to this study, lockdown and other mitigation strategies implemented during the pandemic were not found to be associated with drug use. A limitation of this study is the cross-sectional design, as a result, a larger multicenter study is needed to ascertain the possible association between lockdown, depressive symptoms, and drug use among students.